1993
DOI: 10.1111/j.1751-1097.1993.tb09561.x
|View full text |Cite
|
Sign up to set email alerts
|

ISOLATION AND CHARACTERIZATION OF THE PRESUMED PHOTORECEPTOR PROTEIN OF Blepharisma japonicum

Abstract: Abstract— Photosensory responses in the ciliated protozoan Blepharisma japonicum are mediated by a hypericin‐like chromophore, blepharismin, localized in granules distributed under the cell membrane. A blepharismin‐binding protein, with an apparcnt molecular weight ranging between 35 and 38 kDa, has been isolated by means of column separations and preparative isoelectric focusing and characterized by means of gel electrophoresis, analytic isoelectric focusing as well as absorption and fluorescence spectroscopy. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…3, right series of lanes). Such a low quantity of proteins in these fractions (in the order of nanograms, based on sensitivity of protein silver staining) is consistent with the observed ratio of 280:600 nm absorbance in the chromatography elution profile of this material, characteristic of the purified chromophore (8,9).…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…3, right series of lanes). Such a low quantity of proteins in these fractions (in the order of nanograms, based on sensitivity of protein silver staining) is consistent with the observed ratio of 280:600 nm absorbance in the chromatography elution profile of this material, characteristic of the purified chromophore (8,9).…”
Section: Resultssupporting
confidence: 82%
“…Both Matsuoka et al (8) and Gioffré et al (9) reported the absorbance spectrum of blepharismin in an organic solvent, and the absorbance spectrum of a purified cell extract in water (in the presence of a detergent) containing the putative chromophore apoprotein of B. japonicum. The spectrum reported in Matsuoka et al (8) shows a remarkable scattering component; max of the chromophore was found to be conserved, and the A 280 /A 588 ratio slightly increased (9). This is not in favor with the presence of a chromophore-apoprotein adduct since the hypothetical protein should have a low A 280 , as compared with the pigment, to maintain the A 280 /A 588 ratio.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The data were analyzed by means of the freeware software Imagej (rsb.info.nih.gov/ij), originally developed by NIH (Bethesda, MD, USA). F. salina, B. japonicum, and S. coeruleus were grown as described elsewhere (Marangoni et al, 1996;Gioffré et al, 1993;Walker et al, 1979). Blue B. japonicum was obtained by exposing cells to white light of about 10 W/m 2 for about 24 h.…”
Section: Methodsmentioning
confidence: 99%
“…The blepharismin pigment has been reported to be either non-covalently bound to an apoprotein of molecular mass 38 000 dalton (Gioffre et al, 1993;Yamazaki et al, 1993b) or covalently bound to a molecular weight 200,000 protein (Matsuoka et al, 1993). Fabczak et al (2001) reported that phosphorylation of two other proteins, 28and 46-kDa proteins, of B. japonicum is down-and up-regulated by light, respectively.…”
Section: Ciliate Photoreceptorsmentioning
confidence: 99%